Attitude to e–learning among newly qualified doctors. (February 2014) - Goh, Jason; Clapham, Michael
Summary Background e–Learning plays an increasingly important role in medical education. Much research has focused on the evaluation of individual modules among medical students or more senior trainee doctors. We studied the attitude of newly qualified foundation level–1 doctors (FY1s) towards a blended learning programme to gain insight into the perceived role of e–learning in relation to classroom and experiential learning. Method The blended learning strategy consisted of weekly 3–hour sessions of lectures and flexible e–learning sessions. A questionnaire survey was conducted among 54 per cent (37/69) of FY1 doctors, towards the end of their first year post qualification. Results The majority of FY1s had to carry out additional e–learning outside of work. When asked where was best to carry out e–learning, 54 per cent preferred to e–learn both at work and at home, whereas 38 per cent preferred to e–learn outside of work exclusively. An equal preference for a classroom‐only strategy and a blended programme was reported. Seventy‐three per cent of the FY1s thought that e–learning should not be part of their compulsory weekly teaching programme. Fifty‐four per cent of FY1s thought that e–learning had been useful for their education and training in their FY1 year. The e–learning package cited as being most useful was the safe prescribing e–programme, pioneered locally. Conclusion Newly qualified doctors value e–learning as an adjunct to experiential and lecture‐based teaching, and most prefer it as part of a blended learning programme at work or at home. Medical educators must place equal emphasis on the delivery and administration of e–learning as well as on the course design.